Prevalence and Outcomes of Pre-eclampsia and its Related Factors in Referral Hospital of Ayatollah Mosavi in Zanjan-Iran - sanaz Fayazi; Mina Mousavi; Zahra Moradi; Mahnaz Keshavarz Afshar; Mojdeh Banaei; Fatemeh Bayat (Zanjan University of Medical Sciences and Health Services, 2019)
Background: The study of the prevalence, reasons, and various outcomes of pre-eclampsia in any region is of special importance in determining the prevention and medication strategies in that area. Objectives: This study focuses on the prevalence and outcomes of pre-eclampsia and related factors in the referral Hospital of Ayatollah Mosavi in Zanjan Province. Methods: This cross-sectional and analytical study was conducted on all the pregnant women who delivered their babies in Ayatollah Mosavi Hospital in Zanjan from September 2018 and March 2019. From among 1340 mothers in this study, 63 patients were considered as the sample based on the aim of this study, and 63 participants were selected by means of systematic randomized sampling and were placed in the control group. The data were collected using a researcher-made checklist. Analyses of the data were done using Mann-Whitney U test, Chi-square test, and Fisherchr('39')s exact test (p<0.05). Results: This study proved that the majority of the mothers fell within the age range group of 20-35 (74.6%) characterized by multipar (66.6%). The results showed that the prevalence of pre-eclampsia in Zanjan Province was 5.5 percent. Based on the data, the pre-term and caesarean deliveries by mothers afflicted with pre-eclampsia were found to be 2.5 and 2.86 times, respectively (p<0.05). Furthermore, the experimental group babies needed the NICU care, which was 6.9 percent more than those of the control group (p<0.001). Conclusion: Due to the high prevalence of pre-eclampsia in Zanjan Province and the unfavorable outcomes such as preterm delivery, caesarean, and baby's need for admission in the NISC, it seems that the medication and prevention strategies in the province should be under more review and investigation.